Kinerja Kelompok Lumbung Pangan Kabupaten Ciamis - Ramdan, Mochamad; Sujaya, Dedi Herdiansah; Pardani, Cecep; Djuliansah, Dedi (AGRITEKH (Jurnal Agribisnis dan Teknologi Pangan), 2024)
Institutional performance is defined as the ability of an institution to use its resources efficiently and produce output that is in line with its objectives and relevant to the needs of its users. The main problems often faced by food barns in Ciamis Regency include weak institutional capacity and low participation, so this research aims to determine the performance of Food Barn Groups in Ciamis Regency. The type of research used in this research is the survey method. The data collected includes primary data and secondary data. Respondents were drawn using a simple random method. The number of respondents was 57. To determine the performance of food barns, they were divided into 3 categories, namely high, medium and low, and descriptive analysis was carried out. The results of the research show that the performance of the Food Granary Group in Ciamis Regency is in the high category. The level of institutional structure, clarity of rules, knowledge and participation of members is included in the high category, while the level of achievement is included in the medium category, this shows that the achievements targeted by the food barn are not optimal. The food barn's target achievement was not optimal due to the food barn members getting harvest results (production) that were less than optimal and the same as the previous year. Production is less than optimal due to pest attacks and erratic rainfall.